1992
DOI: 10.1038/sj.bdj.4808026
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the ultrastructure of glass-ionomer (poly-alkenoate) cement

Abstract: Set glass-ionomer cements were sectioned with a diamond knife and examined in the transmission electron microscope. Their appearance was in accordance with the theoretical structure of these materials, close examination revealing glass particles surrounded by a siliceous layer set in a hydrogel matrix. The elemental composition of each region was determined by X-ray microanalysis (energy dispersive). The results of microanalysis supported the ultrastructural observations, with ions that originated from the gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 0 publications
2
24
0
2
Order By: Relevance
“…Meanwhile, they attributed the hardening reaction to the silica component which leached from the glass powder and formed a hydrated silicate in the matrix [34,35]. These results were supported by Cattani-Lorente et al [47] and Hatton and Brook [48], who concluded that the strengthening of CGPCs during maturation resulted from additional cross-linking and the development of a silica gel phase. It is presumed that restricted chain pullout and increased cross-linking are the most likely causes of increased strength while the inorganic phase acts as a reinforcing phase in the strength of CGPCs [2,31].…”
Section: The Role Of Paa During Cgpc Maturationsupporting
confidence: 78%
See 1 more Smart Citation
“…Meanwhile, they attributed the hardening reaction to the silica component which leached from the glass powder and formed a hydrated silicate in the matrix [34,35]. These results were supported by Cattani-Lorente et al [47] and Hatton and Brook [48], who concluded that the strengthening of CGPCs during maturation resulted from additional cross-linking and the development of a silica gel phase. It is presumed that restricted chain pullout and increased cross-linking are the most likely causes of increased strength while the inorganic phase acts as a reinforcing phase in the strength of CGPCs [2,31].…”
Section: The Role Of Paa During Cgpc Maturationsupporting
confidence: 78%
“…PAA concentration < 38% w/w resulted in no effects on the P:L ratio. Working time [38][39][40][41][42][43][44][45][46][47][48][49][50] Within this active region, increasing the PAA concentration decreased the working time. This corresponds to the increased viscosity of the cement.…”
Section: Active Region Commentmentioning
confidence: 99%
“…Firstly, during setting a marked exothermic reaction occurs that may result in thermal damage to the surrounding tissues [5] and second, the release of methyl methacrylate monomer into the tissues may cause chemical necrosis [6]. A novel group of ionomeric cements (ICs) based on a neutralization reaction between aluminosilicate glass and organic polyalkenoic acid are being developed for use as bone cements [1,3,7]. Preliminary trials using ICs for the reconstruction of the middle ear [1,3,8] and for the repair of craniofacial defects [9] have suggested that these cements have few side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of these carboxylate salts might be faster in the water-containing allin-one adhesive investigated, due to the better ionization of 4-AET. Based on the morphological manifestation of a siliceous hydrogel layer around the periphery of FASG fillers, it was indisputable that a GI-type acid-base reaction occurred between the acidic resin monomers and glass fillers 89) . The presence of a surface interaction layer on top of a partially demineralized zone along the resin-dentin interface suggested that either a GI-type reaction or precipitation of insoluble carboxylate salts around remnant apatite crystallites could have occurred when this single-step adhesive interacted with dentin.…”
Section: Ultramorphological Characterization Of the Resindentin Intermentioning
confidence: 99%